Konstitusi Hijau Perancis: Komentar atas asas Kehati-hatian dalam Piagam Lingkungan Perancis 2004 - Wibisana, Andri G. (Jurnal Konstitusi, 2011)
France is the first country that incorporates the precautionary principle into its constitution, via the 2004 Charter for the Environment. Based on the way the principle is formulated in the Charter,  this paper attempts to show whether such an incorporation of the principle into French Constitution should be welcome as a progressive move. In addition, the paper demonstrates how the precautionary principle has been developed and adopted in various international environmental agreements or declarations. The paper also compares the French version of the principle with the development of the precautionary principle in Indonesian environmental law. The papers shows that interpreting the precautionary principle as  risk assessment is not consistent with the intention of developing the precautionary principle, because risk assessment as currently conducted  is plagued with a technocratic approach. The practices of risk assessment have oversimplified the situation of incertitude as merely risk, and consequently, has the potential to ignore public opinion and participation in the decision making process. In this sense, the French version of the precautionary principle is not quite progressive. In contrast, one Indonesian interpretation of the precautionary principle has moved beyond the issue of risk assessment. Such an interpretation, stemming from the court rulings on the Mandalawangi case, combines the precautionary principle with strict liability, by imposing liability to those who fail to take precautionary measures against uncertain  damage.